â€œMosukuru To Eyaâ€ Uncovering The Local Cultural Values Behind Profit - Mohamad Anwar Thalib (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2023)
Purpose: This study aims to find the value of local wisdom behind income accounting practiced by traders in Gorontalo food stalls.Method: This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and good deeds.Results: The study found that traders earn higher income on Thursday and Sunday nights. Meanwhile, traders experienced a decrease in their income during the Covid 19 pandemic. Traders used their income to finance operational, personal, and charity business needs. The income accounting practice lives with gratitude to God (mosukuru to Eya). In Islamic culture, elders often internalize these values through lumadu "diila o'onto, bo wolu-woluwo" which means invisible but there.Implications: The implication of this research is that it is an effort to preserve local culture-based income accounting.Novelty: This study presents the concept of income accounting based on local cultural values of the Gorontalo people.